Randai Malin Nan Kondang: From Kaba to Musical Performance - Wenhendri, Wenhendri; Firdaus, Firdaus (Institut Seni Indonesia Padangpanjang, 2024)
Randai Minangkabau is a medium to convey kaba or folklore through gurindam or sung poetry and galombang (dance) derived from the movements of silat Minangkabau. Randai Malin Nan famous as a vehicle over Kaba Malin Kundang as an important performing arts musical developed in the present era. Using the method of ekranization or transfer process is done by applying the principle of ekranization as a unity of dramatic embodiment. Randai Malin Nan famous, is expected to be a performing arts creativity that considers didactic aspects, critical aspects, and aspects of entertainment in one whole.